EKSEKUSI TERHADAP JAMINAN FIDUSIA PADA PT. FEDERAL INTERNASIONAL FINANCE CABANG JAKARTA - , Arundina Larasati; , R.A. Antari Innaka T, S.H., M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of research, entitled \"Execution of Fiduciary Collateral in PT. Federal International Finance, Jakarta Branch\" is to know the juridical analysis regarding process of executing of the fiduciary collateral and to know inhibiting factors and way of dealing the obstacles in the process of execution of fiduciary collateral that occurred in PT. Federal International Finance This research is an empirical legal research, which is based on secondary data such the basic norms, basic rules, legislation, books, articles, etc., then continued with research on primary data in the field or on the community. All data were analyzed with qualitative methods. Sampling conducted with the Non-Random Sampling technique, as for the type of sample that is used in this research is purposive sampling.. The results showed that various perception given by the parties among others by the legal staff of PT. FIF and debtors of PT. FIF. Fiduciary execution in PT. FIF Jakarta Branch conducted pursuant to Article 29 paragraph (1) letter c Fiduciary Act (Undang-Undang Jaminan Fidusia) by way of underhand sales. Inhibiting factors in the execution of fiduciary PT. FIF are lack of understanding of the debtors regarding fiduciary, framing fiduciary certificate in the middle of the credit period, and the bad faith of the consumer. Way of dealing the inhibiting factors in the process of execution of fiduciary are introduction about the fiduciary thoroughly and deeply to the debtors, the inclusion of a statement of willingness to framing fiduciary certificate in the middle of the credit period, and prevention and control gradually to avoid bad faith committed by debtors who experienced bad credit.